Women in Mycenaean Greece : The Linear B Tablets from Pylos and Knossos - Olsen, Barbara Ann (Taylor and Francis, 2014)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- Acknowledgements -- Conventions of Linear B -- 1 The women of Mycenaean Greece -- 2 Identifying and contextualizing women in the tablets -- 3 Women and production at Pylos -- 4 Women and property holdings at Pylos -- 5 Women at Knossos: production and property -- 6 Women and land tenure at Pylos and Knossos -- 7 Women and religion at Knossos and Pylos -- 8 Conclusions: women in Aegean prehistory -- Appendix A: All mentions of women in the Pylos Tablets -- Appendix B: All mentions of women in the Knossos Tablets -- Bibliography -- Subject index -- Tablet index.